The Relationship of Gratitude with Subjective Well-Being In Social Media Addicts - Sari, Suci Rahmita; Utami, Rahayu Hardianti (Causalita, 2024)
This study aims to look at the relationship between gratitude and subjective well-being in social media addicts. The research method used in this study is quantitative with a correlational approach. The research sample consists of addictive social media users with an age level of 18-24 years and using social media Instagram and Tiktok. Data collection applies the use of the Satisfaction With Life Scale (SWLS) and the Positive Affect Negative Affect Schedule (PANAS) for measurement of subjective well-being components. Gratitude measurement applies the use of The Gratitude Questionnaire-Six Item Form (GQ-6) scale which has been adapted to the Indonesian language. Meanwhile, Bergen Social Media Addiction (BSMAS) is used to identify addictive social media users. Correlation test technique through product moment technique was used as a method in analyzing research data. The results show that there is no relationship between gratitude and life satisfaction, while subsequently there is a positive relationship between gratitude and the affective component in social media addicts. This study provides potential implications in further studies on the dynamics of the relationship that occurs between gratitude and components of subjective well-being specifically in social media addicts.